Podocan Promotes Differentiation of Bovine Skeletal Muscle Satellite Cells by Regulating the Wnt4-β-Catenin Signaling Pathway - Li, Shuang; Liu, Dan; Fu, Yuying; Zhang, Chunyu; Tong, Huili; Li, Shufeng; Yan, Yunqin (Frontiers in Physiology, 2019)
Background: Small leucine-rich repeat proteins (SLRPs) are highly effective and selective modulators of cell proliferation and differentiation. Podocan is a newly discovered member of the SLRP family. Its potential roles in the differentiation of bovine muscle-derived satellite cells (MDSCs) and its underlying functional mechanism remain unclear. Our study aimed to characterize the function of the podocan gene in the differentiation of bovine MDSCs and to clarify the molecular mechanism by which podocan functions in order to contribute to a better understanding of the molecular mechanism by which extracellular matrix promotes bovine MDSC differentiation and provide a theoretical basis for the improvement of beef quality. Methods: Bovine MDSCs were transfected with vectors to overexpress or inhibit podocan, and podocan protein was added to differentiation culture medium. qRT-PCR, western blotting, and immunofluorescence were performed to investigate the effects of podocan on MDSC differentiation. Confocal microscopy and western blotting were used to assess the nuclear translocation and expression of β-catenin. An inhibitor and activator of β-catenin were used to assess the effects of the Wnt/β-catenin signaling pathway on MDSC differentiation. We inhibited β-catenin while overexpressing podocan in MDSCs. Then, we performed mass spectrometry to identify which proteins interact with podocan to regulate the Wnt/β-catenin signaling pathway. Finally, we confirmed the relationship between podocan and Wnt4 by co-immunoprecipitation and western blotting. Results: Podocan protein expression increased significantly during bovine MDSC differentiation. Differentiation of bovine MDSC was promoted and suppressed by podocan overexpression or inhibition, respectively. Podocan was also shown to modulate the Wnt/β-catenin signaling pathway. Treatment of bovine MDSCs with β-catenin inhibitor and activator showed that the Wnt/β-catenin pathway is involved in bovine MDSC differentiation. Furthermore, the effect of podocan on bovine MDSC differentiation was suppressed when this pathway was inhibited. We also found that podocan interacts with Wnt4. When Wnt4 was inhibited, podocan-induced promotion of bovine MDSC differentiation was attenuated through Wnt/β-catenin signaling. Conclusion: Podocan regulates Wnt/β-catenin through Wnt4 to promote bovine MDSC differentiation.